Selecting quality management and improvement initiatives: case studies of industries in Thailand - Thawesaengskulthai, Natcha (2007)
Many organisations invest a considerable amount of capital and resources, implementing new techniques to improve their operating performance. Many approaches and techniques are available. New fashionable methods tend to displace older approaches, which may still have value. An effective strategy for selecting and implementing improvement initiatives is an important issue to ensure stakeholder satisfaction. This research aims to investigate quality management and continuous improvement practices, study and analyse several approaches leading to continuous improvement (CI), then construct a framework to assist senior management teams, by providing a decision aid for selecting improvement initiatives. Six key improvement approaches including Total Quality Management (TQM), Six Sigma, ISO9001, Business Process Reengineer (BPR), Lean production (Lean), Business Excellence framework (BE) were selected as the focus in this study.